Síntese de novos híbridos moleculares entre a estrutura privilegiada 7-cloroquinolina e adutos de morita-baylis-hillman candidatos a fármacos antitumorais e antiparasitários - Oliveira, João Paulo Gomes de (2019)
The importance of the quinolinic nucleus is related to its applicability in several pharmacological targets, making it an attractive substructure for the rational development of new drug candidates. Therefore, we propose in this work the synthesis and bioevaluation of hybrids derived from 7-chloroquinoline and Morita-Baylis-Hillman (AMBH) nitrosubstituted adducts as potential drug candidates using the aid of saturated spacers of different dimensions, ranging from two to four carbons in order to observe the influence of conformational freedom on the biological activity of synthesized structures. The first stage of the work was to prepare 2-5 alcohols with yields between 94% and 98%, by means of an aromatic nucleophilic substitution reaction; followed by the formation of intermediate acrylates 6-9 with yields between 43% and 99%, using two methodologies, via the Steglich reaction (DCC / DMAP) or by the formation of the halogenated intermediate, with yields and as a last step, the reaction of Morita-Baylis-Hillman with satisfactory yields varying between 33% and 74%, generating a total of 9 new substances (3 acrylates and 6 AMBH). Biological tests were performed in vitro on Leishmania amazonensis strain and on cancer cell lines of MCF-7 (breast cancer), HCT-116 (colorectal cancer), HL-60 (chronic myeloid leukemia) and NCI-H292 (lung cancer). The results were promising both on the part of the hybrid adducts with IC50 = 5.06μM for tumor cells and IC50 = 22.12μM for leishmania strains and on the part of the intermediates observing IC50 = 14.76μM for tumor cells and IC50 = 12.97μM for strains of leishmania, suggesting possible influence of spacers on biological activity.